Desenvolvimento humano em atividade: Há unidade?”: transvisões da pergunta No devir da pesquisa com crianças – uma Análise autoscópica em contexto de Educação infantil - Bica, Mariane Oliveira (2019)
The processes of continuous training of Basic Education teachers that are made combined to the academic researches linked to the postgraduate stricto sensu courses, are increasingly being considered as possibilities for the development of formal education. This happens because the Basic Education teacher who dedicates himself to the research, especially when aiming his/her teaching activity, develops formative and investigative trajectories vectors of qualification both of the school scope and of the educational research, given the praxiological character of the process of continuous formation teachers-researchers. this perspective, this dissertation presents itself as an artifact constituted in a process of continuous teacher training. In this perspective, this Dissertation presents itself as an artifact constituted in a process of continuous teacher training. This study is an ethnographic approach that, intermediated by the autoscopic analysis (LAROCCA, 2002), presents itself as a formative narrative of a teacher-researcher who investigates her teaching activity in a context of Early Childhood Education in a class of Pre-School I (children aged 4 years old) from a public school in Passo Fundo - RS. The research process, combined with the qualification process of pedagogical work, aimed to contribute to the integral development of children by means that also enabled children to become protagonists and, therefore, children-researchers in the course of the investigation. The study was part of a shared research project on the discursive interactions in Early Childhood Education, developed by the Group of Studies and Research on Literacy, in which resulted, in addition to this work, a thesis and two dissertations, presented to the Postgraduate Program in Education of the University of Passo Fundo. Based on the analyzes of the three other investigations, which recognized a peculiar human development in that children's school community, the kids and the teacher-researcher, equipped with their cameras and their field diary, traced a research course that sought to identify the microgenetic unit of human development in that space/time. With the aid of the microgenetic analysis, based on the Historical-Cultural Theory, three instances of meaning about development were identified during the autoscopic processes ofthe produced data: the dialogical instance, of responsive sense; the space-time, of institutional sense; and the instance of experience valued in doubt, of authorial sense. Inan m interchange with theoretical references especially related to the historical-cultural, sociodiscursive and sociocultural field, namely, Vigotsky (2009) and Leontiev (1988), Bakhtin (2011), Bruner (2001) and Rogoff (2005), with the products of the shared research, namely, Bragagnolo (2016), Camargo (2016) and Sartori (2016), the question was recognized as the microgenetic unit of human development, the premise and product of the basic sense of development in that children’sschool community. The question is understood, then, as an enunciative act that, committed to the immediate cultural situation, takes up (the tone) and goes back (with emotional -volitional tonality) a peculiar verbal action of a historically valued intonation.